Utilization of the National Health Insurance Healthy Indonesia Card (JKN KIS) in Negeri Liang, Central Maluku Regency - Hans Sammy Marthin Salakory; Hafis Makayaino; Mohammad Dahlan Sely; Febby Sonya Matuulessy; Luthfy Latucinsina (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
The National Health Insurance Healthy Indonesia Card (JKN KIS) is Indonesia?s primary system for achieving Universal Health Coverage. Although many people nationwide are enrolled, use remains limited in rural areas such as Negeri Liang in Central Maluku. This study explores factors affecting JKN KIS utilization by assessing residents? knowledge, access to information, attitudes, and social influences within rural communities. A cross-sectional survey of 189 residents from Liang Village used a structured questionnaire focusing on four latent constructs. Data analysis employed Partial Least Squares?Structural Equation Modeling (PLS-SEM) in SmartPLS, with 5,000 bootstrapped resamples (two-tailed) to evaluate reliability, validity, and predictive relevance through loadings, AVE, CR, HTMT, R?, f?, and 95% confidence intervals. Results show that knowledge (β = 0.308, 95% CI: 0.182?0.442; f?= 0.147), access to information (β= 0.251, 95% CI: 0.118?0.389; f?= 0.104), and attitude (β= 0.357, 95% CI: 0.217?0.497; f?= 0.187) significantly and positively influence JKN KIS use, with attitude being the most impactful factor. Social influences, however, were not significant (β= 0.051, p= 0.388; f?= 0.004), indicating a limited direct effect. The structural model exhibits moderate explanatory power (R?= 0.482). In conclusion, participation in JKN KIS in rural areas is mainly driven by internal cognitive and emotional factors, rather than social influences. To boost engagement, strategies should focus on enhancing public knowledge, improving access to trustworthy information, and fostering positive attitudes. Policy recommendation: primary healthcare centers should prioritize attitude-oriented education and counseling, emphasizing financial protection and service benefits, with the aim of at least a 15% increase in valid JKN KIS claims within one year.?Keywords: Health Insurance Utilization, Knowledge, Information Access, Attitude, Social Factors?